Expression of a Splice Variant of CYP26B1 in Betel Quid-Related Oral Cancer - Ping-Ho Chen; Ka-Wo Lee; Cheng-Chieh Hsu; Jeff Yi-Fu Chen; Yan-Hsiung Wang; Ker-Kong Chen; Hui-Min David Wang; Hurng-Wern Huang; Bin Huang (The Scientific World Journal)
Betel quid (BQ) is a psychostimulant, an addictive substance, and a group 1 carcinogen that exhibits the potential to induce adverse health effects. Approximately, 600 million users chew a variety of BQ. Areca nut (AN) is a necessary ingredient in BQ products. Arecoline is the primary alkaloid in the AN and can be metabolized through the cytochrome P450 (CYP) superfamily by inducing reactive oxygen species (ROS) production. Full-length CYP26B1 is related to the development of oral pharyngeal cancers. We investigated whether a splice variant of CYP26B1 is associated with the occurrence of ROS related oral and pharyngeal cancer. Cytotoxicity assays were used to measure the effects of arecoline on cell viability in a dose-dependent manner. In vitro and in vivo studies were conducted to evaluate the expression of the CYP26B1 splice variant. The CYP26B1 splice variant exhibited lower expression than did full-length CYP26B1 in the human gingival fibroblast-1 and Ca9-22 cell models. Increased expression of the CYP26B1 splice variant was observed in human oral cancer tissue compared with adjacent normal tissue, and increased expression was observed in patients at a late tumor stage. Our results suggested that the CYP26B1 splice variant is associated with the occurrence of BQ-related oral cancer.